Critical evaluation of faunistic data: Three species of monotrysian moths (Eriocraniidae, Prodoxidae and Incurvariidae) erroneously reported from Russia - Kozlov MV (PENSOFT PUBL, 2025)
The published records of Eriocrania chrysolepidella Zeller, 1851, Incurvaria koerneriella (Zeller, 1839) and Lampronia aeneella (Heinemann, 1870) from Chuvash and Karelia Republics in Russia are based on misidentified specimens. This finding, along with earlier reports on the widespread occurrence of errors, even in the most authoritative works, calls for a critical approach to published data in order to stop sp reading and citing false information across future publications.